2021
DOI: 10.1021/acs.est.0c07681
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Adsorption of Humic Substances on Graphitic Carbon Nitride

Abstract: Graphitic carbon nitride (CN) has been widely used in environmental pollution remediation. However, the adsorption of organic compounds on CNs, which has practical significance for the environmental application of CNs, is poorly understood. For the first time, this study systematically investigated the adsorption behaviors and mechanisms of humic substances (HSs), i.e., humic acid (HA) and fulvic acid (FA), on CNs derived from four typical precursors. Intriguingly, CN derived from urea (CN-U) showed a great ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 75 publications
1
28
1
Order By: Relevance
“…After TC adsorption, there was a significant change of C = C peak shape, implying the aromatic C = C of HAs/KMBC might be combined with the benzene ring of TC. The O 1 s spectra of 10% HAs/KMBC was deconvoluted into three peaks at 530.92 eV, 532.32 eV and 532.74 eV, corresponding to the Fe–O, C–O, and C = O groups, respectively 29 , 38 . After TC uptake, the shift of C–O and C = O groups indicated that the hydroxyl and carboxyl groups of HAs/KMBC might be combined with the carbonyl and hydroxyl groups of TC, demonstrating that hydrogen bond might play a role in the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…After TC adsorption, there was a significant change of C = C peak shape, implying the aromatic C = C of HAs/KMBC might be combined with the benzene ring of TC. The O 1 s spectra of 10% HAs/KMBC was deconvoluted into three peaks at 530.92 eV, 532.32 eV and 532.74 eV, corresponding to the Fe–O, C–O, and C = O groups, respectively 29 , 38 . After TC uptake, the shift of C–O and C = O groups indicated that the hydroxyl and carboxyl groups of HAs/KMBC might be combined with the carbonyl and hydroxyl groups of TC, demonstrating that hydrogen bond might play a role in the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…UCN and NS-DCN have less negative surface charge than other CNs, for example, DCN, TCN, and MCN. 12,52 Hemolysis Effect of CN In Vitro. The hemolysis assay was used to evaluate the cytotoxic effect of CN on biological membranes.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…2,3 Physical disruptions of the cell membrane are dominated by direct contact with nanoparticles, and lipid bilayers are damaged through mechanical rupture or adsorption extraction of lipid molecules. 8−10 Recently, graphitic carbon nitride (g-C 3 N 4 , CN) has attracted considerable attention in a variety of fields, including environmental remediation, 11,12 energy conversion, 11,13 and biomedicine, 14,15 due to its unique nanostructure and physical properties. 16 With the promising future of CN in various applications, it is necessary to assess its biocompatibility and possible nanotoxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of humic substances will bring a series of problems in textile dyeing wastewater treatment. For example, increasing the chroma of water, [ 40 ] causing the blockage and reducing the utilization of membrane, [ 41,42 ] reducing the adsorption capacity of activated carbon, [ 43 ] leading to the breeding and reproduction of microorganisms in the drainage network, [ 44 ] reducing the pipeline life, and generating toxic by‐products by combining with chlorine in the disinfection process. [ 45 ] We chose humic acid (HA) solution to simulate the main dissolved organic matters in textile dyeing wastewater.…”
Section: Introductionmentioning
confidence: 99%